Ruang Publik dan Modal Sosial: Privatisasi dan Komodifikasi Ruang di Kampung - Setiawan, Bobi B. (Unisia, 2010)
This article describes that village is understood as a form of comunal housing, and there is a public space. It is needed the public intervension in keeping and developing the existence of public space in villages in Indonesia. The forms of intervension is suggested. But, it is important to note that the public space in villages in Indonesia can be developed by management process based on the village communities. The public space and social capital are interrelated each other- the public space prepares to support social capital, and the existence of public space needs one grade of certain social capital.